Differentiated Learning by Style Enhances Self-Regulation and Science Achievement in Fourth Grade Students - Mariske, Edeh Dike; Anggraini, Adinda Tabyta; Maryani, Ika (The Indonesian Institute of Science and Technology Research, 2025)
This study investigates the influence of differentiated instruction, tailored to students' learning styles, on self-regulation and science learning outcomes among fourth-grade elementary students. Utilizing a quasi-experimental design, the research involved an experimental group that received differentiated instruction based on students’ learning styles through Project-based Learning (PjBL) model, and a control group taught through Problem-based Learning (PBL) model. Data were collected using validated instruments and analyzed using normality and homogeneity tests, as well as independent and paired sample t-tests, through SPSS version 30. Findings indicate that differentiated instruction significantly improved students’ science learning outcomes, as evidenced by a higher posttest mean score in the experimental group compared to the control group. Although the independent t-test showed a significant difference in self-regulation between the groups, the paired sample t-test did not reveal a significant increase in self-regulation within the experimental group itself. These results suggest that while differentiated instruction effectively enhances academic achievement in science, its impact on self-regulation is less pronounced. The study underscores the value of learner-centered instructional approaches that address individual learning differences to optimize educational outcomes in primary science education.